2022
DOI: 10.1002/app.52114
|View full text |Cite
|
Sign up to set email alerts
|

Self‐roughened superhydrophobic polydopamine coating with excellent self‐cleaning, anti‐corrosion, and UV shielding performances

Abstract: Various strategies have been developed to fabricate superhydrophobic surfaces with the guidance of adding rough micro-nano structure and decreasing surface energy. However, it is still a challenge to prepare a superhydrophobic coating with multifunction, eco-friendliness, and broad applicability to substrates. The mussel-inspired polydopamine (PDA) possessing superior material-independent adhesion was considered as the promising candidate material. Herein, a hierarchical superhydrophobic PDA coating was fabric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Recently, polydopamine (PDA) has been receiving immense attention because it can strongly adhere to a variety of substrates, irrespective of smooth or rough substrates under a wet environment. [1][2][3] In 2007, Messersmith et al 4 were inspired by mussel and first carried out selfpolymerization of dopamine (DA) with excellent adhesion properties and the ability of deposition onto various substrates such as metals, [5][6][7] oxides, polymers, 8,9 ceramics even including classically adhesion-resistant materials such as polytetrafluoroethylene (PTFE) 10 under aerobic and alkaline conditions. More importantly, the PDA could be easily further modified by Michael addition and Schiff base reaction due to the large amount of catechol moieties of 3,4-dihydroxy-L-phenylalanine and amino group of lysine on its surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, polydopamine (PDA) has been receiving immense attention because it can strongly adhere to a variety of substrates, irrespective of smooth or rough substrates under a wet environment. [1][2][3] In 2007, Messersmith et al 4 were inspired by mussel and first carried out selfpolymerization of dopamine (DA) with excellent adhesion properties and the ability of deposition onto various substrates such as metals, [5][6][7] oxides, polymers, 8,9 ceramics even including classically adhesion-resistant materials such as polytetrafluoroethylene (PTFE) 10 under aerobic and alkaline conditions. More importantly, the PDA could be easily further modified by Michael addition and Schiff base reaction due to the large amount of catechol moieties of 3,4-dihydroxy-L-phenylalanine and amino group of lysine on its surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…30 Furthermore, the successful preparation of a micro-/ nanoscale system requires PDA spheres as a hierarchical structure for constructing superhydrophobic coatings. For example, Yang et al 31 prepared a superhydrophobic PDA coating for using self-cleaning, anti-corrosion, and UV shielding fields. Zhang et al 32 reported a design and fabrication of superhydrophobic fabrics for efficient oil−water separation combining DA self-polymerization and a sol−gel method.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, PDA has been widely employed for the surface modification of various materials . Notably, PDA has physicochemical properties similar to those of eumelanins and contributes to the UV-shielding and radical-scavenging functions, which can protect the skin from UV rays by scavenging free radicals and preventing their penetration into the skin. , Thus, these promising features make PDA-containing gels ideal candidates as safe and efficient UV-shielding materials. …”
Section: Introductionmentioning
confidence: 99%